A SOCIAL COST BENEFIT ANALYSIS OF EXTENDING AN EXISTING RECYCLING PLANT TO ACCOMMODATE THE RECYCLING OF THE PLASTIC FRACTION OF CABLE SCRAP - du Preez, M; Lottering, T (The South African Journal of Industrial Engineering, 2009)
This paper investigates the economic efficiency of extending an existing cable waste